AUTOMATION OF CALCULATIONS BY DEFINITION OF CLASSES OF ROLLING STOCK AND THE CONDITIONS OF ITS PASSES ON BRIDGES - Borshchov, V. I.; Klymov, V. I. (Science and Transport Progress, 2005)
The work considers the contents and structure of the program “CARRIAGE” intended for determination of classes of any rolling-stock operated or planned for introduction into circulation on the railway network of CIS and Baltic countries.